2019
DOI: 10.1186/s12884-019-2671-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D plasma concentrations and VDR gene variants and the risk of premature birth

Abstract: Background: Premature birth is the main cause of mortality in children under 1 year, and vitamin D deficiency during gestation is associated with prematurity. The effects of vitamin D are mediated by its receptor, which is encoded by the VDR gene. VDR variants-such as single nucleotide variation (SNV)-are associated with increased risk of prematurity, but there are conflicting results. We evaluated serum vitamin D concentrations and the frequency of TaqI/A > G, BsmI/C > T, ApaI/C > A, and FokI/A > T VDR varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
(68 reference statements)
0
11
0
1
Order By: Relevance
“…These discrepancies could arise due to the methods of measuring vitamin D and the myriad of confounding variables among the observational studies, including ethnicities and baseline 25(OH)D levels of the subjects [40]. Other researchers found that vitamin D receptor also plays an important role in determining maternal and neonatal health [41,42]. Vitamin D receptor polymorphisms related to FokI, ApaI, and TaqI were reported to be associated with gestational diabetes mellitus, pre-preeclampsia, and preterm birth (reviewed in [43]).…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies could arise due to the methods of measuring vitamin D and the myriad of confounding variables among the observational studies, including ethnicities and baseline 25(OH)D levels of the subjects [40]. Other researchers found that vitamin D receptor also plays an important role in determining maternal and neonatal health [41,42]. Vitamin D receptor polymorphisms related to FokI, ApaI, and TaqI were reported to be associated with gestational diabetes mellitus, pre-preeclampsia, and preterm birth (reviewed in [43]).…”
Section: Discussionmentioning
confidence: 99%
“…Among the most frequently examined VDR gene variants (FokI, rs2228570; ApaI rs7975232; Bsml rs1544410; TaqI, rs 731236), ApaI, BsmI, and TaqI genotype are in linkage disequilibrium in Caucasian populations ( Knabl et al, 2017 ). In several studies these VDR SNPs increased the risk of preterm birth ( Rosenfeld et al, 2017 ; Dutra et al, 2019 ). As determined in a meta-analysis, the here investigated VDR polymorphism (syn.…”
Section: Discussionmentioning
confidence: 99%
“…Budhwar et al reported that VD deficiency disturbed homeostasis of the inflammatory response in the placenta, activating the cytokine network and followed by spontaneous premature preterm delivery [57]. At the same time, Dutra et al observed a correlation between maternal VD levels and VDR gene polymorphisms, as well as the risk of premature birth [58]. No less interesting was the observation that maternal VD serum level was associated with infant birthweight among both white and black women [59,60].…”
Section: Vdr Protein Level In Placentasmentioning
confidence: 99%